Education and Communicating Positive Young Minds in Creating Sustainable Environment and Development - Mohd Idrus Mohd Masirin; Norashikin binti Abdul Hamid; Adnan Zainorabidin; Che Hasnah binti Mahmood; Akmal bin Abdul Rahman; Raha binti Abdul Rahman; Mohamad Sukri bin Mustapa (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: Proposed course content for each group age is outlined from the early age of a child to the university education system. However, these course contents are a recommendation which indicates the importance of continuity to ensure that the young generations will subsequently not only aware of preserving the environment and its surroundings but, will also work hard to improve the existing situation of the world for a quality environment and a better place to live. Design/methodology/approach: These programs and activities include the awareness and sensitivity to the depleting greens, flora, and fauna, the climatic change due to human activities, and the pollution to soil and groundwater. Humans, animals, and other living things rely greatly on soil, water air, and the sun. Findings: Thus, it is critical to inculcate better understanding and creating a more caring society to ensure the sustainability of the earth for the future existence of mankind. Research limitations/implications: In this paper, a discussion on the need of introducing environmental geotechnics to young generations as early as in the pre-school education is deemed necessary as being conducted by most developed countries. Practical implications: Developing countries such as Malaysia must start now to ensure that existing resources such as its soils and groundwater quality are preserved as the country continue to strive in becoming a developed and modern country by the year 2020. Originality/value: Claim your originality here. Paper type: Research paper.